Phenotyping sensory nerve endings in vitro in the mouse - Zimmermann, Katharina; Hein, Alexander; Hager, Ulrich; Kaczmarek, Jan Stefan; Turnquist, Brian P.; Clapham, David E.; Reeh, Peter (Nature Protocols, 2009)
This protocol details methods to identify and record from cutaneous primary afferent axons in an isolated mammalian skin-saphenous nerve preparation. The method is based on extracellular recordings of propagated action potentials from single-fiber receptive fields. Cutaneous nerve endings show graded sensitivities to various stimulus modalities that are quantified by adequate and controlled stimulation of the superfused skin with heat, cold, touch, constant punctate pressure or chemicals. Responses recorded from single-fibers are comparable with those obtained in previous in vivo experiments on the same species. We describe the components and the setting-up of the basic equipment of a skin-nerve recording station (few days), the preparation of the skin and the adherent saphenous nerve in the mouse (15-45 min) and the isolation and recording of neurons (approximately 1-3 h per recording). In addition, stimulation techniques, protocols to achieve single-fiber recordings, issues of data acquisition and action potential discrimination are discussed in detail.
CRIS-Team Scopus Importer:2021-07-19